2005
DOI: 10.1287/mnsc.1040.0298
|View full text |Cite
|
Sign up to set email alerts
|

An Econometric Analysis of Inventory Turnover Performance in Retail Services

Abstract: Inventory turnover varies widely across retailers and over time. This variation undermines the usefulness of inventory turnover in performance analysis, benchmarking, and working capital management. We develop an empirical model using financial data for 311 publicly listed retail firms for the years 1987--2000 to investigate the correlation of inventory turnover with gross margin, capital intensity, and sales surprise (the ratio of actual sales to expected sales for the year). The model explains 66.7% of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
391
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 345 publications
(429 citation statements)
references
References 24 publications
34
391
2
2
Order By: Relevance
“…In this study, we use logIT (log of inventory turnover) as a dependent variable that is developed in Gaur et al (2005) in which a log-linear relationship is suggested between variables. We use the same variables from Gaur et al (2005)-logGM (log of gross margin), logCI (log of capital intensity), and logSS (log of sales surprise)-and add some more independent variables.…”
Section: Data and Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we use logIT (log of inventory turnover) as a dependent variable that is developed in Gaur et al (2005) in which a log-linear relationship is suggested between variables. We use the same variables from Gaur et al (2005)-logGM (log of gross margin), logCI (log of capital intensity), and logSS (log of sales surprise)-and add some more independent variables.…”
Section: Data and Modelmentioning
confidence: 99%
“…We use the same variables from Gaur et al (2005)-logGM (log of gross margin), logCI (log of capital intensity), and logSS (log of sales surprise)-and add some more independent variables. We add a dummy variable Rank that attains the value of 1 if a firm is in the Information Week 500 rankings and gets 0 otherwise.…”
Section: Data and Modelmentioning
confidence: 99%
See 3 more Smart Citations